2023
DOI: 10.1002/pssa.202200791
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Assessment of Compositional Variation for Uncovering High‐Efficiency Improved Stable All‐Inorganic Lead‐Free Perovskite Solar Cells

Abstract: The quest for suitable material technology becomes an imperative aspect of PV energy conversion applications. Pursuing ideal materials or designing efficient PV devices requires a keen understanding of underlying PV action and material properties. These include defect-free, chemically and mechanically stable, semiconductive, and absorption properties, which could be easily tuned, manipulated, and readily fabricated. The candidate for such a futuristic material could be a perovskite solar cell (PSC), which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…[5] The rapid and spontaneous oxidation of Sn 2þ to Sn 4þ during crystallization releases holes in the valence band, leading to strong p-type doping and destabilizing the device's p-i-n configuration. [6][7][8][9][10][11] Recent literature reports suggested that substituting Pb 2þ with mixed Ge-Sn could effectively solve the lead toxicity issue on the one hand and the long-term stability on the other. [12][13][14][15] This mixed Sn-Ge cation at the B site in ABX 3 perovskite has improved ambient, thermal, and photostability while preserving excellent photophysical and wide-bandgap tunability properties of perovskite.The peculiar, enhanced stability of tinÀgermanium Sn-Ge alloyed perovskite such as CsSn 0.5 Ge 0.5 I 3 is due to the introduction of Ge.…”
mentioning
confidence: 99%
“…[5] The rapid and spontaneous oxidation of Sn 2þ to Sn 4þ during crystallization releases holes in the valence band, leading to strong p-type doping and destabilizing the device's p-i-n configuration. [6][7][8][9][10][11] Recent literature reports suggested that substituting Pb 2þ with mixed Ge-Sn could effectively solve the lead toxicity issue on the one hand and the long-term stability on the other. [12][13][14][15] This mixed Sn-Ge cation at the B site in ABX 3 perovskite has improved ambient, thermal, and photostability while preserving excellent photophysical and wide-bandgap tunability properties of perovskite.The peculiar, enhanced stability of tinÀgermanium Sn-Ge alloyed perovskite such as CsSn 0.5 Ge 0.5 I 3 is due to the introduction of Ge.…”
mentioning
confidence: 99%
“…R S should remain below 1 Ω cm 2, and R Sh must be above 1 k Ωcm 2 for efficient device functioning. The empirical relation gives the dependence of device J – V characteristic on R S and R Sh [ 24 ] I=IphIs(eqV+IRsnkT1)V+IRsRSh$$I = I_{\text{ph}} - I_{\text{s}} \left(\right. e^{\frac{q V + I R_{\text{s}}}{n k T}} - 1 \left.\right) - \frac{V + I R_{\text{s}}}{R_{\text{Sh}}}$$ V is the applied voltage, I ph is the light generated current, I s , n , K , and T are the reverse saturation current, ideality factor, Boltzmann constant, and temperature, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[16] SCAPS is a 1D Poisson solver package for simulating solar devices, available from the University of Gent, Belgium, Department of Electronics and Information Systems (ELIS), by Marc Burgelman et al [17] SCAPS-1D results have good coherence between experimental and simulation results with an error margin of less than 10 À15 . [18] It can model thin-film polycrystalline solar cells like CdTe, [19] CIGS, [20] CZTS, [21] SnS, [22] FeS 2 , [23] perovskite [24,25] etc. SCAPS solves three basic differential semiconductor equations (Poisson equation and continuity equation for both holes and electrons) at the interface/contact of the device structure.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation